Determinant Factors of Patient Satisfaction in the Orthopedic Surgery Ward - Hastara Dewi, Kenwi; Pratiwi, Arum; Alis Setiyadi, Noor (JKG (JURNAL KEPERAWATAN GLOBAL), 2024)
Background: Patient satisfaction is a crucial measure of health service performance. The fluctuations in this level of accomplishment can serve as empirical evidence for developing quality and patient safety programs. This study seeks to assess and analyse demographic characteristics, the degree of patient satisfaction, and the relationship between respondent characteristics and satisfaction at three orthopedic surgery wards over a span of three time periods: 2021 to 2023. Methods: This study employs a quantitative research methodology adopting a descriptive comparative technique. The independent variables of this study were time period, quality dimensions, and patient characteristics. The dependent variable of this study was patient satisfaction. The data were examined using Kruskal-Wallis’s analysis, the central tendency, and multiple regression analysis. Results: The study showed that the level of patient satisfaction has increased every year (p-value = 0.005), with no significant difference between the three wards (p-value = 0.893). Also, there is no significant correlation with patient satisfaction for each year (p-value > 0.05). Nevertheless, the findings of this study indicate that age significantly influences patient satisfaction in 2021 (p-value = 0.021) and 2023 (p-value = 0.007). Conclusion: It is recommended this research be expanded by exploring other patient characteristic variables and exploring the key elements that significantly influence patient satisfaction in many patient care settings.